2013
DOI: 10.2147/imcrj.s51572
|View full text |Cite
|
Sign up to set email alerts
|

Chronic idiopathic axonal neuropathy and pain, treated with the endogenous lipid mediator palmitoylethanolamide: a case collection

Abstract: Chronic idiopathic axonal polyneuropathy is a frequent diagnosis in patients suffering from idiopathic polyneuropathy and neuropathic pain. No guidelines exist on how to treat these patients. To date, there are no results available from randomized clinical trials, and mostly classical neuropathic analgesics are prescribed, such as amitriptyline and gabapentine. However, the usefulness of these drugs is limited, as many patients remain in pain despite treatment, or suffer debilitating side effects. Palmitoyleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…PEA is a pleiotropic mediator and modulator, having an effect on several receptors ( Figure 1 ) [ 52 ]. Its efficacy and tolerability have been documented in over 40 clinical trials in around 5000 patients and its side-effect profile is very benign [ 53 , 54 ]. However, due to the fact that PEA is available as a nutraceutical, its therapeutic potential is not well recognized in the medical field yet.…”
Section: Palmitoylethanolamide: Early Insights In Anti-inflammatormentioning
confidence: 99%
“…PEA is a pleiotropic mediator and modulator, having an effect on several receptors ( Figure 1 ) [ 52 ]. Its efficacy and tolerability have been documented in over 40 clinical trials in around 5000 patients and its side-effect profile is very benign [ 53 , 54 ]. However, due to the fact that PEA is available as a nutraceutical, its therapeutic potential is not well recognized in the medical field yet.…”
Section: Palmitoylethanolamide: Early Insights In Anti-inflammatormentioning
confidence: 99%
“…PEA exerts antinociceptive effects in several animal models [ 16 , 17 ]. Its safety and efficacy were shown in a variety of clinical trials focused on pain state treatment: diabetic neuropathy, carpal tunnel syndrome, dental and temporomandibular joint pain, and arthritic, postherpetic, and chemotherapy-induced neuropathic pain [ 18 , 19 ]. Moreover, PEA protects nervous tissue in neuropathic conditions [ 20 ], prevents neurotoxicity and neurodegeneration [ 21 , 22 ], and inhibits peripheral inflammation and mast cell degranulation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might be of importance, since certain TRPV1 channel activators have been recently patented for the treatment of muscular cramps [10]. PEA has been evaluated in a number of placebo controlled randomized clinical trials and has been found to be effective in various neuropathic pain states and inflammation [11][12][13][14]. PEA is produced in the body on demand, as all lipid autacoids, and accumulates locally during inflammatory and pain disorders.…”
Section: Discussionmentioning
confidence: 99%